2013
DOI: 10.1097/tp.0b013e3182a1618c
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Pneumocystis Pneumonia in Renal and Liver Transplant Patients Caused by Genotypically Distinct Strains of Pneumocystis jirovecii

Abstract: Background An outbreak of 29 cases of Pneumocystis jirovecii pneumonia (PCP) occurred among renal and liver transplant recipients (RTR and LTR) in the largest Danish transplantation centre between 2007 and 2010, when routine PCP prophylaxis was not used. Methods P. jirovecii isolates from 22 transplant-cases, 2 colonized RTRs and 19 Pneumocystis-control samples were genotyped by restriction fragment length polymorphism and multi-locus sequence typing analysis. Contact tracing were used to investigate transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 36 publications
0
77
0
4
Order By: Relevance
“…This conclusion seems robust because, as shown by the phylogenetic tree, data for the three loci combined were sufficient to discriminate between 24 unrelated P. jirovecii isolates (10). To our knowledge, this is the first genotypic demonstration of clustered PCP limited only to liver transplant patients (24), whereas numerous studies have reported similar findings for kidney recipients (6,10,18), especially in France (10). Thus, in accordance with recent works regarding SOT (26), our study suggests that the use of prophylaxis as widely practiced in most centers of kidney transplantation (22,26) should also be considered thoroughly for liver recipients.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This conclusion seems robust because, as shown by the phylogenetic tree, data for the three loci combined were sufficient to discriminate between 24 unrelated P. jirovecii isolates (10). To our knowledge, this is the first genotypic demonstration of clustered PCP limited only to liver transplant patients (24), whereas numerous studies have reported similar findings for kidney recipients (6,10,18), especially in France (10). Thus, in accordance with recent works regarding SOT (26), our study suggests that the use of prophylaxis as widely practiced in most centers of kidney transplantation (22,26) should also be considered thoroughly for liver recipients.…”
Section: Discussionmentioning
confidence: 69%
“…It should be noted that our institution did not apply systemic anti-PCP chemoprophylaxis for liver transplant patients because the incidence of this opportunistic infection had always remained lower than 0.01 (two cases among 285 patients over 4 years). Indeed, although it has been shown that the risk of acquiring PCP may increase in SOT recipients not taking effective prophylaxis (6,23,24), routine prophylaxis is recommended only for centers with an incidence of PCP of at least 3 to 5% among transplant recipients (25). In such health care settings, trimethoprim-sulfamethoxazole remains the drug of choice (80 to 160/400 to 800 mg orally daily or three times weekly [grade I] for at least 6 to 12 months posttransplantation [grade III]) (26).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that anti-CD20 inhibits T-cell priming against P. murina. (22). It is still not known why CD20 ϩ B cells specifically are required to prime CD4 ϩ cell responses to Pneumocystis.…”
Section: Discussionmentioning
confidence: 99%
“…have a dynamic extracellular proteome as a result of varying their major surface glycoproteins, which may be used to evade the host immune response (26,27). Reports of large genetic variability between Pneumocystis jirovecii isolates also suggest the possibility that patients are simply being exposed to new strains of Pneumocystis (22,28).…”
Section: Cd20mentioning
confidence: 99%
“…Molecular typing methods, such as restriction fragment length polymorphism (RFLP) analysis, multiple locus sequence typing, direct DNA sequencing, and variable number of tandem repeats (VNTRs), have been used to analyze the epidemiology of P. jirovecii. A number of independent genomic regions, including the mitochondrial large subunit rRNA (mtLSU rRNA), the rRNA internal transcribed spacer (ITS), the intron of the nuclear 26S rRNA (26S), thymidylate synthase (TS), the variable region of the mitochondrial 26S rRNA gene (mt26S), dihydropteroate synthase (DHPS), dihydrofolate reductase (DHFR), the region surrounding intron number 6 of the btubulin gene (b-tub), superoxide dismutase (SOD), cytochrome b (CYB), thioredoxin reductase (Trr1), 5-enolpyruvylshikimate-3-phosphate synthase (AROM), kexin-like serine protease (Kex1), and upstream conserved sequence (UCS) of the major surface glycoprotein (MSG) gene, have been used to analyze the genetic diversity of P. jirovecii (Esteves et al, 2009(Esteves et al, , 2010Gupta et al, 2013;Rabodonirina et al, 2013;Rostved et al, 2013;Wakefield, 1998). However, among these regions, the ITS, because of its high degree of genetic variation, might be the most discriminatory region for differentiating P. jirovecii isolates (Gupta et al, 2010;Le Gal et al, 2012).…”
Section: Introductionmentioning
confidence: 99%